Impression management analysis of South African State-Owned Enterprises: six capitals disclosure in the chairman, CEO, CFO and Performance Report - Shaikh, Sumaiyabanu (My University, 2022)
Orientation: State-Owned Enterprises (SOEs) in developing economies, such as South Africa, have a critical economic, social, and environmental influence. However, South African SOEs are currently dealing with increased public scrutiny, putting their organisational legitimacy in jeopardy as they continue to drain public funds. As a result, SOEs may find it difficult to defend their value relevance and may resort to impression management strategies to maintain their legitimacy. Research Purpose: The purpose of this study is to analyse if certain impression management techniques, namely attribution, neutralisation, and thematic manipulation, are employed by Schedule 2 South African SOEs in specific sections of their integrated reports. The study also aims to understand the use of the six capitals in SOEs’ integrated reports and the application of impression management techniques to the six capitals. Significance of study: This study could benefit society at large, as users could factor impression management into their decisions. There is currently limited research regarding impression management in the public sector. This study contributes to the body of literature on impression management within the public sector in an emerging economy. Overview of Research Method: The SOEs analysed are those included in Schedule 2 of the Public Finance Management Act (PFMA). Within the integrated report, the focus is on the Chairman, CEO, CFO Statements, and the Performance Report. A qualitative approach, using content analysis with the data being analysed using quantitative methods, was adopted. Main Findings: The findings of this study highlight that SOEs engage in some form of impression management (either through thematic manipulation, attribution, or neutralisation) when presenting the six capitals. SOEs employ assertive impression management through the technique of thematic manipulation to gain legitimacy and employ defensive impression management through the techniques of attribution and neutralisation to repair legitimacy. Despite the challenges that SOEs have faced over the two years, the narratives disclosed create a notion of optimism to achieve legitimacy, and this is accomplished by managing the impression of the words in the Chairman, CEO, CFO and Performance Reports.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: SOEs; Impression management; Attribution; U CTD; SDG-8: Decent work and economic growth